2006
DOI: 10.1007/s00253-006-0526-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of two intracellular β-glucosidases belonging to glycoside hydrolase family 1 from the basidiomycete Phanerochaete chrysosporium

Abstract: cDNAs encoding two glycoside hydrolase family 1 beta-glucosidases (BGL1A and BGL1B) were cloned from the basidiomycete Phanerochaete chrysosporium, and the substrate specificities of the recombinant enzymes and the expression patterns of the two genes were investigated in relation to cellobiose metabolism by the fungus. The cDNA sequences contained open reading frames of 1,389 base pairs (bp) (bgl1A) and 1,623 bp (bgl1B), encoding 462 and 530 amino acids, respectively. Although high sequence identity (65%) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 33 publications
6
37
0
1
Order By: Relevance
“…This fungus contains up to nine LPMOs known to be expressed when grown on lignocellulosic substrates (12,59). Because extensive work has been done on other model glycoside hydrolase (65)(66)(67)(68) and dehydrogenase enzymes (69,70) from P. chrysosporium, the P. chrysosporium LPMOs offer an excellent model system to understand the need for multiple oxidative activities to degrade biomass. The PchGH61D structure revealed potentially important residues around the active site and putative binding surface that may impart differences in LPMO specificity and activity.…”
Section: Discussionmentioning
confidence: 99%
“…This fungus contains up to nine LPMOs known to be expressed when grown on lignocellulosic substrates (12,59). Because extensive work has been done on other model glycoside hydrolase (65)(66)(67)(68) and dehydrogenase enzymes (69,70) from P. chrysosporium, the P. chrysosporium LPMOs offer an excellent model system to understand the need for multiple oxidative activities to degrade biomass. The PchGH61D structure revealed potentially important residues around the active site and putative binding surface that may impart differences in LPMO specificity and activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of cel7C, for example, expression was upregulated by 2 h of cultivation in the presence of cellobiose, cellotriose, or cellotetraose, and at that time point, larger amounts of glucose residue had been assimilated in cellotriose or cellotetraose culture than in cellobiose culture. In P. chrysosporium, hydrolysis of cellooligosaccharide may be mainly catalyzed by intracellular BGL (BGL1B) rather than extracellular BGL (BGL3A) (49). The catalytic efficiency (k cat / K m ) of BGL1B is much greater for cellotriose (21 ϫ 10 1 s Ϫ1 mM Ϫ1 ) and cellotetraose (16 ϫ 10 1 s Ϫ1 mM Ϫ1 ) than for cellobiose (75 s Ϫ1 mM Ϫ1 ) (T. Tsukada et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Calculation of the cLogP (low value indicates high water solubility) revealed that the two sequential glycosylation reactions supporting the conversion of geraniol into geranyl-pri are associated with a stepwise increase in hydrophilicity, from 2.97 to 2.00 (geranyl-glc) and from 2.00 to 0.46 (geranyl-pri). The cLogP value significantly depends on the sugar type at the nonreducing end as well as the sugar number (Tsukada et al, 2006). Furthermore, the existence of exoglycosidases that cleave disaccharide primeverose into Glc and Xyl has not been established in tea plant or other plants.…”
Section: Putative Physiological Roles Of Csgt1 and Csgt2 In Volatile mentioning
confidence: 99%